2014
DOI: 10.1007/s13277-014-2429-4
|View full text |Cite
|
Sign up to set email alerts
|

Synuclein-gamma predicts poor clinical outcome in esophageal cancer patients

Abstract: The synuclein gamma (SNCG) protein, a member of neuronal protein family synuclein, has been considered as a promising potential biomarker as an indicator of cancer stage and survival in patients with cancer. The present study was conducted to evaluate the prognostic value of SNCG in patients with esophageal carcinoma (EC). SNCG levels were assessed immunohistochemically in cancer tissues from 73 EC patients. Median age was 57 (range, 29-78) years old. Forty-seven percent of the patients were male. Thirty-seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Synuclein-γ ( SNCG ) is the third member of the synuclein family [6], which is strongly associated with malignant progression and distant metastasis in different types of cancer. SNCG protein is abnormally expressed in a high percentage in various malignant tumor tissues including liver, breast, ovarian, prostate and colon cancer, while it is rarely expressed in tumor-matched non-neoplastic adjacent tissues [7, 8]. Cumulative findings suggest that SNCG might be a potential biomarker in cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Synuclein-γ ( SNCG ) is the third member of the synuclein family [6], which is strongly associated with malignant progression and distant metastasis in different types of cancer. SNCG protein is abnormally expressed in a high percentage in various malignant tumor tissues including liver, breast, ovarian, prostate and colon cancer, while it is rarely expressed in tumor-matched non-neoplastic adjacent tissues [7, 8]. Cumulative findings suggest that SNCG might be a potential biomarker in cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…The SNCG protein was not interacting with any of the other proteins from the pathway, yet its down-regulation occurred in more than 75% of the CRC samples. Increased expression of the SNGG gene was suggested to be a predictor of poor prognosis in esophageal or endometrial cancer patients [ 37 , 38 ], which is distinct from the negative regulation observed here. SFRP1 , from the Wnt pathway, was strongly down-regulated in all CRC samples of this study, like most of the genes from the pathway, as opposed to the WNT2 and the CCND1 genes, which were increased in more than 75% of the CRC samples, agreeing with previous results [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 69%
“…It was reported that γ-synuclein expression is dysregulated in oral squamous cell carcinoma [14], esophageal cancer [15], and breast cancer [16]. The α-synuclein protein shows distinct tissue distributions and is predominantly expressed in brain tumors and melanomas [8, 9, 17].…”
Section: Discussionmentioning
confidence: 99%